Effects of intracerebral hemorrhage on 5-hydroxymethylcytosine modification in mouse brains - Tang Y; Han S; Asakawa T; Luo Y; Han X; Xiao B; Dong Q; Wang L (Neuropsychiatric Disease and Treatment, 2016)
Yilin Tang,1,* Sha Han,1,* Tetsuya Asakawa,2,3 Yunhe Luo,1 Xiang Han,1 Baoguo Xiao,4 Qiang Dong,1,4 Liang Wang1,41Department of Neurology, Huashan Hospital of Fudan University, Shanghai, People’s Republic of China; 2Department of Neurosurgery, 3Department of Psychiatry, Hamamatsu University School of Medicine, Hamamatsu, Shizuoka, Japan; 4Institute of Neurology, Huashan Hospital of Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this workAbstract: The past decade has resulted in an increase in the knowledge of molecular mechanisms underlying brain injury induced by intracerebral hemorrhage (ICH). Recent advances have provided a link between epigenetic modification and the regulation of gene expression. 5-hydroxymethylcytosine (5hmC) converted from 5-methylcytosine by the ten-eleven translocation (TET) family of proteins has emerged as a new epigenetic modification. While the dynamics of 5hmC during cerebral ischemia have recently been reported, whether 5hmC is involved in ICH remains unexplored. In this study, we investigated the effects of ICH on DNA hydroxymethylation. We showed that the global level of 5hmC rapidly decreased as early as 24 hours after ICH and persisted until 72 hours. Furthermore, the level of 5hmC in the CpG-rich regions of Akt2, Pdpk1 and Vegf genes was significantly decreased with a minimum level observed at 48 hours or 72 hours. Decreased 5hmC was observed in parallel with an increase in 5-methylcytosine over this time course, and mRNA levels of Akt2, Pdpk1 and Vegf were downregulated upon ICH injury. Finally, Tet1, Tet2 and Tet3 mRNA levels were dramatically decreased in the ICH brain. Our study for the first time established the correlation between DNA hydroxymethylation and ICH injury. Further investigations should examine whether 5hmC modification could be a therapeutic target for the treatment of ICH injury.Keywords: stroke, cerebral edema, DNA hydroxymethylation, TET protein